Tabbiejack

What is the solution of the system? Use substitution.
x = –2y + 10
–6y = 6x – 6
z = –3x + 10y
A. x = 9, y = –8, z = 114
B. x = –8, y = 9, z = 114
C. x = –8, y = 114, z = 9
D. x = 114, y = 9, z = –8

Delete
Share
This Question is Closed

Tabbiejack

Best Response

You've already chosen the best response.

0
@.Sam.

.Sam.

Best Response

You've already chosen the best response.

0
When x = –2y + 10 ,
From
–6y = 6x – 6
–6y = 6( –2y + 10 ) – 6
Solve for y

Tabbiejack

Best Response

You've already chosen the best response.

0
? I such at this

Tabbiejack

Best Response

You've already chosen the best response.

0
so its C

.Sam.

Best Response

You've already chosen the best response.

0
\[–6y = 6( –2y + 10 ) – 6 \\ \\ -6y=-12y+60-6 \\ \\ 6y=54 \\ \\ y=9\]
Get it?

Tabbiejack

Best Response

You've already chosen the best response.

0
no

.Sam.

Best Response

You've already chosen the best response.

0
You distribute 6 into brackets
\[–6y = 6( –2y + 10 ) – 6\]
\[-6y=-12y+60-6\]
Add 12y to both sides,
6y=54
Divide both sides by 6
y=9

Tabbiejack

Best Response

You've already chosen the best response.

0
both sides of what

Tabbiejack

Best Response

You've already chosen the best response.

0
I don't understand this at all and slopes forget it

.Sam.

Best Response

You've already chosen the best response.

0
|dw:1367472748738:dw|

Tabbiejack

Best Response

You've already chosen the best response.

0
ok the answer is A